PERENCANAAN STRUKTUR GEDUNG KANTOR OTORITAS JASA KEUANGAN (OJK) KAWASAN REGIONAL 4 DENGAN METODE BETON PRACETAK - Dwi Oktavianto; Nurul Rochmah (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
This study aims to plan the structure of the Regional Financial Services Authority Office Building 4 East Java using precast concrete. The use of precast concrete is based on advantages in terms of economy, efficiency, speed of implementation, and energy consumption that have an impact on the environment. The precast concrete structure is designed by assuming the structure is monolithic cast in place. Precast elements require joints that function to transfer the forces that occur between elements. Planning refers to the guidelines that apply in Indonesia, namely SNI 1727:2020, SNI 1726:2019, and SNI 2847:2019. Based on the results of the analysis obtained the configuration of the structure, the dimensions of each structural element, and the connection between the structural elements. The connection uses a combination of dry and wet joints which aims to produce a monolithic structure. The connection between the column and the column uses 4 PEC® Column Shoe, the connection between the main beam and the sub-beam uses a combination of corbel, 2 BECO® Beam Shoe at the bottom of the main beam, and a rebar coupler that connects the top reinforcement of the main beam. The connection between the beams and the main beam uses 2 BECO® Beam Shoes at the bottom of the beams and distribution reinforcement at the top of the beams. The connection of the slab to the beam uses joint reinforcement at the top and bottom of the slab.